Le centre public d’une agglomération secondaire de la cité des Médiomatriques : Bliesbruck (Moselle) - Jean-Paul Petit; Sara Santoro (Gallia)
The small town of Bliesbruck – of unknown name – is established in the eastern part of the civitas of the Mediomatrici, in the Blies valley that it shares with a large axial plan villa located at Reinheim (Saarland, Germany). From 2008 to 2013, programmed excavations took place in the public centre and permitted to carry out an extensive study and to reconstruct its chronological evolution. It is a large square situated between the monumental public thermal complex and the main road, along which three buildings are set – a monumental fountain in the middle, a three-aisled basilica and a series of shops on the sides. It is structured by a circulation system of which the coherence is connected to the adaptation of the buildings servicing. The public centre develops progressively from the end of the 1st-early 2nd centuries AD. Built towards the end of the 2nd century-early 3rd century, the basilica fits in with an overall rebuilding program leading to a real urban scenography. The presence of this central space from the early Empire raises the question of the town status that presently we just have to define as a small town.